The Relationship Between Dietary Patterns and the Incidence of Overweight among Adolescents - Hidayah, Rahmah Nur; Nuradhiani, Annisa; Bohari, Bohari (Journal of Health and Nutrition Research, 2024)
This study employed a cross-sectional design to investigate the association between dietary patterns and the occurrence of overweight status in urban adolescents. A total of 124 respondents were recruited using purposive sampling. Data collection involved anthropometric measurements and completion of the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) using a self-administered questionnaire method. The study findings revealed that 29% of adolescents experience overweight status. Most frequent food consumption occurs in staple foods (82.3%), animal protein (73.4%), plant-based protein (63.7%), fats (82.3%), and vegetables (50.8%). Conversely, infrequent consumption was observed for fruits (58.9%), snacks (68.5%), fast food (71.8%), and beverages (55.6%). Furthermore, deficits are prevalent in energy (44.4%), protein (46.8%), and carbohydrates (60.5%), while excess intake is seen in fats (57.3%). Respondents exhibit predominantly low physical activity (66.9%). Chi-square tests indicate significant associations between consumption frequency in the plant-based protein and vegetable groups (p ≤ 0.05) and between energy intake and macronutrients (p ≤ 0.05) with overweight status.